β-glucan as a new tool in vaccine development - Vetvicka, Vaclav; Vannucci, Luca; Sima, Petr (Scandinavian journal of immunology, 2020)
Vaccination constitutes one of the major breakthroughs in human medicine. At the same time, development of more immunogenic vaccine alternatives to using aluminium-based adjuvants is one of the most important phases of vaccination development. Among different sources of carbohydrate polymers, including plants, microbes and synthetic sources tested, glucans were found to be the most promising vaccine adjuvant, as they alone stimulate various immune reactions including antibody production without any negative side effects. The use of glucan particles as a delivery system is a viable option based on the documented efficient antigen loading and receptor-targeted uptake in antigen-presenting cells. In addition to particles, soluble glucans can be used as novel hydrogels or as direct immunocyte-targeting delivery systems employing novel complexes with oligodeoxynucleotides. This review focuses on recent advances in glucan-based vaccine development from glucan-based conjugates to a glucan-based delivery and adjuvant platform.
Keywords: vakcíny; vakcinace; Humans; oligodeoxyribonukleotidy; Adjuvants, Immunologic; hydrogely; Vaccination; adjuvancia imunologická; beta-glukany; beta-Glucans; subject; diseases; cancer; Drug Delivery Systems; lidé; zvířata; processes; Antigen Presentation; experimental animals; Vaccines; lékové transportní systémy; Hydrogels; Animals; vaccination; Oligodeoxyribonucleotides; prezentace antigenu